Population increase and “new-build gentrification” in central Tokyo - Lützeler, Ralph (ERDKUNDE, 2008)
Since the second half of the 1990s, population figures started to recover in the central wards of Tky. The suburban hinterland, by contrast, is marked by overall stagnation. This study focuses on the question of how this process is affecting the social composition of the city center, illustrated by the case of Minato ward. It can be demonstrated that Tky is certainly not a “revanchist city” in the sense defined by Neil Smith in his study on New York (1996), nor is it appropriate to interpret the re-urbanization process as a mere return of middle-mass suburbanites, a view that is popular in Japan. Instead, by developing high-rise housing clusters on centrally located brownfield land or newly reclaimed waterfront sites, a gradual and place-selective replacement of the preexisting, socially rather mixed population of central Tky by in-movers who are mainly composed of singles and childless couples (and only in some areas including a larger share of nuclear families) is taking place. Based on the idea of a multi-functional and neatly designed city landscape which can prevail in the competition with other global cities, this process is actively promoted by state authorities as key actors. It is therefore concluded that re-urbanization of central Tky can be put in the context of “new-build gentrification” as defined by Davidson and Lees (2005).